ANALISIS PENILAIAN TINGKAT KESEHATAN PT. BANK NEGARA INDONESIA (PERSERO) TBK. DENGAN METODE RGEC PERIODE 2016-2020 - Muhammad Raihan Rafi Al Azharr (2021)
As a financial institution, the bank has a function as a reservoir and distributor of funds from the public to the community as well as providing other financial services to make it easier for the public to transact. In carrying out its functions, banks need to maintain their level of trust in the eyes of the public. The growth/decrease of public trust in a banking institution is influenced by the soundness of the bank itself. PT. Bank Negara Indonesia (Persero) Tbk. is one of the state-owned enterprises whose business scope has been covered in the international area as evidenced by the opening of 7 branch offices in 6 countries. This study aims to determine the soundness of Bank BNI using the RGEC methods (risk profile, good corporate governance, earning, capital) approach using the RBBR (risk-based bank rating) approach. Then from the results of this paper, it shows that the overall health level of Bank BNI is in the "Very Healthy" predicate based on the data that the authors processed from the financial statements and the implementation of Bank BNI's governance for the 2016-2020 period although there are several components that are recommended to improve the predicate so that the health condition Bank BNI remains stable or increases in the future.